The Insulin Receptor: A New Target for Cancer Therapy - Belfiore, Antonino; Malaguarnera, Roberta (Frontiers in Endocrinology, 2011)
Recent studies have convincingly shown that both the IGF-I receptor (IGF-IR) and the insulin receptor (IR) play a role in cancer development and progression. In particular, overactivation IR by IGF-II is common in cancer cells, especially in dedifferentiated/stem-like cells. In spite of these findings, until recently, only IGF-IR but not IR has been a deliberate target in cancer therapy. Although a variety of preclinical studies have showed a good anti-cancer activity of selective anti-IGF-IR drugs, the results of the clinical first trials have been disappointing. In fact, only a small subset of malignant tumors has shown an objective response to these therapies. Development of resistance to anti-IGF-IR drugs may include IR isoform A upregulation and overactivation by increased levels of autocrine IGF-II in cancer cells. These findings have led to the concept that co-targeting IR together with IGF-IR may increase therapy efficacy and prevent adaptative resistance to selective anti-IGF-IR drugs. IR blockade should be especially considered in tumors with high IR-A:IGF-IR ratio and high levels of autocrine IGF-II. Conversely, insulin sensitizers that ameliorate insulin resistance, associated with metabolic disorders or cancer treatments, may have important implications for cancer prevention and management. Only few drugs targeting the IR are currently available. Ideally, future IR targeting strategies should be able to inhibit the tumor promoting effect of IR without impairing its metabolic effects.